Effects of supplementation with creatine monohydrate and beta-alanine, alone or combined, on repeated sprint performance and physiological parameters in amateur team and racket sport players - Delextrat, Anne (Array, 2020)
The purpose of this study was to compare the combined effects of creatine monohydrate (Cr) and beta-alanine (BA) with their isolated use on performance and physiological parameters during repeated sprint sequences (RSS). Forty-four male (n=34) and female (n=10) amateur team- and racket sport players (25.1±3.1 years; 175.2±9.8 cm; 76.0±10.3 kg; 15.2±6.8% body fat) performed ten repetitions of 6-s sprints with departure every 30 s, before and after a 28-day supplementation period with either Cr (n=11, 5 g‧day-1), BA (n=10, 6 g‧day-1), combined Cr and BA (n=12, 5 g‧day-1 of Cr plus 6g‧day-1 of BA) or placebo (11 g‧day-1 of rice flour). Peak (PP) and mean power (MP), performance decrement (%Dec), heart rate (HR), blood lactate concentration (LA) and perceived exertion (RPE) were measured. Analyses of variance (ANOVA) were used to determine the effects of groups (Cr, BA, CrBA, P), sprint number (1 to 10), and time (pre- vs. post-supplementation) on all variables. A significant increase in PP was shown in the post- compared to the pre-supplementation in Cr (+5.2%) and BA (+5.2%) groups only (p<.05), and significant decreases in MP in all groups (3.7% to 6.4%, p<.05), except BA. %Dec was significantly decreased post-supplementation in the Cr group only (17.4%, p<.05). No effects were shown on HR, RPE and LA (p<.05). These results show no additional benefits of the combination of Cr and BA on RSS performance and suggest that longer sprint or total exercise duration might be necessary to observe the benefits of the combined supplementation.